THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1945)
Abstract How can accounting teachers, individually and through the activities of the American Accounting Association, cooperate most effectively in turning the attention of promising students toward the possibilities existing in an accounting career? The columns of the periodical "The Accounting Review" are open to those who have ideas to contribute and questions to raise. The usefulness to an individual of knowing something of his aptitudes for accounting work is easily appreciated. But the teacher faces certain problems in that connection. It will be particularly difficult to advise those students who are highly capable, since they probably can succeed in any one of a number of occupations. In all fields the most capable newcomers are the most desired. Therefore each teacher may be expected to favor his own field of specialization. Is there any danger that teachers may fall into competitive counseling? Will it be necessary to develop a wide series of aptitude tests pointed toward the various careers visualized in the program of a college of commerce? May it not be that counseling directed toward superior students will result in ignoring the slower students? The advantages of education should not be reserved for an intellectual aristocracy; possibly the best students need the least advice.